A predictive model unifying hydrogen enhanced plasticity and decohesion. (1st July 2022) - Lin, Meichao; Yu, Haiyang; Ding, Yu; Wang, Gang; Olden, Vigdis; Alvaro, Antonio; He, Jianying; Zhang, Zhiliang
Abstract: The detrimental effect of hydrogen on metals which manifests itself as a transition from a ductile to a brittle failure mode is, for the first time, incorporated into a unified continuum-scale predictive framework. The complete Gurson model, designed to predict ductile failure by voiding, is extended to include failure by decohesion. Hydrogen enhanced plasticity is accounted for through acceleration of the voiding process while hydrogen induced decohesion is realized by a degradation of the decohesion threshold. The interplay between these two failure modes driven by hydrogen concentration are well captured. This model can predict a realistic level of embrittlement as well as the suppression of dimples in a hydrogen induced fracture surface. Being generic, versatile, and easy to implement, the model may serve as a basis for interpretation of laboratory experiments and enable the transferability of the laboratory results to the integrity assessment of engineering components in hydrogen environment. Graphical abstract: Image, graphical abstract